Relatório de estágio curricular supervisionado em medicina veterinária - área de reprodução e manejo de bovino corte - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This report describes the activities developed and / or monitored by the academic Rafael Gomes Severo, during the Supervised Curricular Internship in Veterinary Medicine (ECSMV). The internship was carried out between March 2 and June 5, 2015, totaling 560 hours, under the guidance of Professor Fábio Gallas Leivas, covering activities of sanitary and reproductive management in beef cattle. As a place of internship, the company ProCriar was chosen, as it is a company with extensive experience in the areas that were chosen for the internship and also has a good casuistry in the regions of Campanha Ocidental and Santa Maria, in the state of Rio Grande do Sul. The company is headquartered in the city of São Francisco de Assis, RS and the supervision of activities was carried out by Veterinarian Gustavo Felipe Lopes. The activities in the area of ​​sanitary management were the monitoring of the practices of the National Program for the Control and Eradication of Brucellosis and Animal Tuberculosis, while the activities of reproductive management included the monitoring and carrying out of pregnancy diagnosis techniques; fixed-time artificial insemination; orchiectomy in cattle and induction of prepubertal heifers. The realization of the internship in the chosen areas was of paramount importance, as it provided knowledge of numerous realities that are of theoretical knowledge during graduation, allowed him to mature critically in the face of everyday professional situations.
Report of supervised internship report on veterinary medicine - breeding area and management of beef cattle
Keywords: Medicina veterinária; Bovinos; Clínica de grandes animais; Bovinocultura; Veterinary medicine; Cattle; Large animal clinic; Beef cattle; Reprodução animal; Reprodução de bovinos; Biotécnicas de reprodução animal; Animal reproduction; Animal breeding biotechniques; CNPQ::CIENCIAS AGRARIAS